PHYSICAL EDUCATION METHODS USED IN PHYSICAL EDUCATION LESSONS - Raxmatov Davlat Toyirovich (Galaxy International Interdisciplinary Research Journal, 2024)
This article provides information on teaching and training methods used in Physical Education, a general description of physical qualities and pedagogical analysis of control over their development.